First evidence for the decay B0s → μ+μ− - Aaij, Roel; Adametz, Aleksandra; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (Physical review letters, 2013)
A search for the rare decays B0s→μ+μ− and B0→μ+μ− is performed with data collected in 2011 and 2012 with the LHCb experiment at the Large Hadron Collider. The data samples comprise 1.1 fb−1 of proton-proton collisions at √s=8 TeV and 1.0 fb−1 at √s=7 TeV. We observe an excess of B0s→μ+μ− candidates with respect to the background expectation. The probability that the background could produce such an excess or larger is 5.3×10−4 corresponding to a signal significance of 3.5 standard deviations. A maximum-likelihood fit gives a branching fraction of B(B0s→μ+μ−)=(3.2+1.5−1.2)×10−9, where the statistical uncertainty is 95% of the total uncertainty. This result is in agreement with the standard model expectation. The observed number of B0→μ+μ− candidates is consistent with the background expectation, giving an upper limit of B(B0→μ+μ−)<9.4×10−10 at 95% confidence level.
Im Titel sind "0", "+" und "-" jeweils hochgestellt und "s" in B0s tiefgestellt
LHCb Collaboration: R. Aaij, A. Adametz, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 573
Gesehen am 22.03.2021